Dehydration of Alginic Acid Cryogel by TiCl4 vapor: Direct Access to Mesoporous TiO2@C Nanocomposites and Their Performance in Lithium‐Ion Batteries. Issue 12 (6th June 2019) - Kim, Sanghoon; De Bruyn, Mario; Alauzun, Johan G.; Louvain, Nicolas; Brun, Nicolas; Macquarrie, Duncan J.; Stievano, Lorenzo; Mutin, P. Hubert; Monconduit, Laure; Boury, Bruno
Abstract: A new strategy for the synthesis of mesoporous TiO2 @C nanocomposites through the direct mineralization of seaweed‐derived alginic acid cryogel by TiCl4 through a solid/vapor reaction pathway is presented. In this synthesis, alginic acid cryogel can have multiple roles; i) mesoporous template, ii) carbon source, and iii) oxygen source for the TiO2 precursor, TiCl4 . The resulting TiO2 @alginic acid composite was transformed either into pure mesoporous TiO2 by calcination or into mesoporous TiO2 @C nanocomposites by pyrolysis. By comparing with a nonporous TiO2 @C composite, the importance of the mesopores on the performance of electrodes for lithium‐ion batteries based on mesoporous TiO2 @C composite was clearly evidenced. In addition, the carbon matrix in the mesoporous TiO2 @C nanocomposite also showed electrochemical activity versus lithium ions, providing twice the capacity of pure mesoporous TiO2 or alginic acid‐derived mesoporous carbon (A600). Given the simplicity and environmental friendliness of the process, the mesoporous TiO2 @C nanocomposite could satisfy the main prerequisites of green and sustainable chemistry while showing improved electrochemical performance as a negative electrode for lithium‐ion batteries. Abstract : Seaweed batteries ! A simple and eco‐friendly method for direct conversion of seaweed into mesoporous TiO2 @C was developed and used for application in lithium‐ion batteries. The carbon matrix in the mesoporous TiO2@C nanocomposite showed electrochemical activity versus lithium ions, providing twice the capacity of pure mesoporous TiO2 or alginic acid‐derived mesoporous carbon.